Drivers and outcomes of sustainable marketing strategy in the African context: the role of competitive advantage and strategic proactivity as mediating and moderating variables - Girma Tegene Demessie; Amit Shukla (Cogent Business & Management, 2024)
This research focused on sustainable marketing strategies, and their drivers and outcomes in the African context using the perspectives of industrial organizations and the resource-based view. 360 marketing/production managers of manufacturing firms from Ethiopia were contacted for collecting primary data using a structured questionnaire. Research hypotheses were tested using structural equation modeling. Moreover, using the Hayes process macro and 5000 bootstrapping samples, an estimation of mediation and moderation effects was conducted. The findings indicated that managerial resources, relational resources, financial resources, environmental policies, and eco-technology detection and response are instrumental in the implementation of a sustainable marketing strategy. The research also revealed that competitive advantage mediates the influence of sustainable marketing strategy on business performance, indicating a partial mediation. Finally, the study found that strategic proactivity moderates the direct link between sustainable marketing strategy - competitive advantage, and the indirect association between sustainable marketing strategy and business performance via competitive advantage. The study has forwarded practical implications for manufacturing firms in Africa. Management and policymakers need to understand and help develop managers' understanding of the stakeholders' concerns about the environment and the benefits of sustainable marketing strategies (SMS). It is also important to note that implementing SMS proactively helps firms to acquire experience, and skills in sustainable practices that contribute to SMS efficiency and effectiveness, and subsequently achieve cost savings and a reputation for being at the forefront of SMS implementation, which can ultimately create a competitive advantage.
Keywords: 650; sustainable marketing strategy; drivers; outcomes; firm performance; strategic proactivity; competitive advantage; africa